Effect of Roasting Time on Total Phenolic Content and Antioxidant Activity of Cocoa Bean Shells: English - Nadirah B. Andi Pallawa; Miming Berlian Hi. B Salam; Laras Ayu (Faculty of Agriculture, Tompotika Luwuk University, 2026)
Cocoa bean shells are a by-product of cocoa processing that contain bioactive compounds, particularly phenolics, with potential antioxidant activity. However, information on the effect of roasting time on the total phenolic content and antioxidant activity of fermented cocoa bean shells remains limited. Therefore, this study evaluated the effect of roasting time on the total phenolic content and antioxidant activity of fermented cocoa bean shells derived from Forastero cocoa beans (BR 25 variety) from Bolang Village, Enrekang Regency. A laboratory experiment was conducted using a drum roaster with a charge temperature of 135°C and roasting times of 10, 14, 18, and 22 min. Roasting time significantly affected total phenolic content and antioxidant activity. Roasting for 14 min produced the highest mean total phenolic content (30.1425 mg GAE/g extract) and the lowest IC50 value (83.69 ppm), although these results were not significantly different from those at 18 min. In contrast, the 10 and 22 min treatments showed lower total phenolic content and weaker antioxidant activity. These findings suggest that moderate roasting durations, particularly 14–18 min, were more favorable for maintaining the bioactive properties of cocoa bean shells.